Efficacy of hybrid remote neuropsychological rehabilitation on cognitive complaints in post-therapeutic lower-grade glioma: the FREEDOME randomized study protocol - Guerdoux, Estelle; Coutant, Louise; Gourgou, Sophie; Mollevi, Caroline; Duc, Marie-Sophie; Salasc, Fanny; Duffau, Hugues; Darlix, Amélie (Frontiers in Psychology, 2025)
Lower-grade gliomas (LrGGs) are rare tumors that mainly concern young adults, with an overall survival ranging from 5 to 20 years and without any curative treatment to date. LrGGs are frequently associated with psychological disorders and neurocognitive impairments, including memory and dysexecutive syndrome, that can negatively affect professional, familial and social functioning, ultimately reducing the patients' health-related quality of life (HRQoL). Maintaining an acceptable HRQoL is a key objective because survival outcomes tend to be better in patients with fewer psychopathological comorbidities and better HRQoL. Neuropsychological rehabilitation and cognitive behavioral therapy (CBT) have shown promising results in patients with neurological conditions, mental health disorders, and cancer. However, they are not routinely used in patients with LrGG, and onco-neuro-psychologists (i.e., neuro-psychologists trained in oncology) with expertise in neurocognition and CBT are lacking. The aim of this study protocol is to evaluate the efficacy of the remote FREEDOME program, which integrates CBT and a digital neurocognitive tool, in patients with LrGG who experience cognitive complaints post-therapeutic phase. This ongoing, prospective, open-label, multicenter, randomized trial (1:2) should include 187 patients with LrGG considered “stable” (12 months after surgery, 6 months after chemotherapy or radiotherapy) and who are not planned to receive any cancer treatment in the first 4 months after enrollment. The primary objective is to assess the FREEDOME program effects on perceived cognitive impairment at month 4 post-inclusion. Secondary objectives include patient adherence to the intervention, and effects on the subjective and objective neurocognitive functioning, HRQoL (including sleep, fatigue and return-to-work) and psychopathological symptoms over time. The study will also explore the intervention effects on the patient memory and irritability, as perceived by family caregivers. This study may represent an important step in the implementation of evidence-based neuropsychological interventions tailored to the specific needs of patients with LrGG.Clinical trial registrationClinicalTrials.gov: NCT06468176; ID-RCB: 2023-A02376-39.